Before the pool of Narcissus : the Nederduitse Gereformeerde Kerk's journey to confessional orthodoxy and isolation through the lense [sic] of doctrine - Holkeboer, Mieke Rae (Department of Religious Studies, 2015)
Bibliography: leaves 116-122.